A Case of Glycogenic Hepatopathy as a Complication of Poorly Controlled Type 1 Diabetes Mellitus. (29th September 2022) - Munugoti, Samhitha; Reddy, Vamsee; Patel, Gaurav; Gaddam, Maneesh; Abburi, Triveni
Abstract : A 23-year-old African American male with a medical history significant for poorly controlled type 1 diabetes mellitus (T1DM) presented with abdominal pain and vomiting. His laboratory workup was consistent with diabetic ketoacidosis (DKA). An acute elevation of liver enzymes was noted as the DKA resolved, with the alanine transferase and aspartate transferase levels elevated to more than 50 times the normal limit within the next 24 hours. Because abnormal liver function tests are found frequently in patients with type 1 diabetes mellitus, it is important to have a broad differential diagnosis. Furthermore, a low threshold of suspicion is required to identify a relatively underdiagnosed etiology like glycogenic hepatopathy (GH). This case report describes how patterns and trends of liver function tests provide important clues to the diagnosis of GH; how imaging modalities like ultrasonography, computerized tomography (CT) scan, and magnetic resonance imaging (MRI) scan could be used to differentiate GH from nonalcoholic fatty liver disease (NAFLD); and how the diagnosis of GH can be made without the need for invasive liver biopsy. The knowledge about GH should prevent its delayed diagnosis and improve the outcomes by appropriately managing uncontrolled type 1 DM.